If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 55 + -5(3b + -1) = -11 Reorder the terms: 55 + -5(-1 + 3b) = -11 55 + (-1 * -5 + 3b * -5) = -11 55 + (5 + -15b) = -11 Combine like terms: 55 + 5 = 60 60 + -15b = -11 Solving 60 + -15b = -11 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -15b = -11 + -60 Combine like terms: 60 + -60 = 0 0 + -15b = -11 + -60 -15b = -11 + -60 Combine like terms: -11 + -60 = -71 -15b = -71 Divide each side by '-15'. b = 4.733333333 Simplifying b = 4.733333333
| (7-w)(5w-2)=0 | | la+5l=13 | | Ia+5l=13 | | 1/2(8+6)-2=4+x-2 | | 20+50y+x=180 | | x^3+2x^2-70x+13=0 | | 2+ln(x+4)=8 | | x+4-3=8 | | 5x-25+6x+3=180 | | 5i=123 | | 3-2(2-4)=2+2 | | 18x+6y=252 | | 527r=123483 | | (60x+1)(x+25)=0 | | 3-5=2+5 | | 5(6x+5)(2x+1)=0 | | 5(6x-5)(2x-1)=0 | | 30x=-2x^2-100 | | 7x+2=9x | | 0=(5x-7)(3x-2) | | 17=3(x+5)+8 | | -15.4-15d+22d=4.4 | | 0=(5x+7)(3x+7) | | 0=(15x+2)(x+7) | | (4x-3y)dx+(2y-3x)dy=0 | | 18x^3-6x^2+36x-12=0 | | 2+5=2 | | 5x+3+15x+7= | | 2x^3-10x=0 | | 2x^3-10x= | | -72=5x-6(x+14) | | 1/6-x=1/2 |